Cannabis use, decision making, and perceptions of risk among breastfeeding individuals: the Lactation and Cannabis (LAC) Study - Caroline B. Smith; Jenna Schmidt; Elizabeth A. Holdsworth; Beatrice Caffé; Olivia Brooks; Janet E. Williams; David R. Gang; Mark A. McGuire; Michelle K. McGuire; Celestina Barbosa-Leiker; Courtney L. Meehan (BMC, 2024)
Abstract Objective Our primary objective was to understand breastfeeding individuals' decisions to use cannabis. Specifically, we investigated reasons for cannabis use, experiences with healthcare providers regarding use, and potential concerns about cannabis use. Methods We collected survey data from twenty breastfeeding participants from Washington and Oregon who used cannabis at least once weekly. We documented individuals' cannabis use and analyzed factors associated with their decisions to use cannabis during lactation. Qualitative description was used to assess responses to an open-ended question about potential concerns. Results Fifty-five percent of participants (n = 11) reported using cannabis to treat or manage health conditions, mostly related to mental health. Eighty percent of participants (n = 16) reported very few or no concerns about using cannabis while breastfeeding, although participants who used cannabis for medical purposes had significantly more concerns. Most participants (n = 18, 90%) reported receiving either no or unhelpful advice from healthcare providers. Four themes arose through qualitative analysis, indicating that breastfeeding individuals are: 1) identifying research gaps and collecting evidence; 2) monitoring their child's health and development; 3) monitoring and titrating their cannabis use; and 4) comparing risks between cannabis and other controlled substances. Conclusions Breastfeeding individuals reported cannabis for medical and non-medical reasons and few had concerns about cannabis use during breastfeeding. Breastfeeding individuals reported using a variety of strategies and resources in their assessment of risk or lack thereof when deciding to use cannabis. Most participants reported receiving no helpful guidance from healthcare providers.